Responses of mediterranean freshwater invertebrates to the fungicide difenoconazole across different macrophyte dominance conditions: A mesocosm study - Daniel Grillo-Avila; María Antón-Pardo; Javier Armengol; Eric Puche; Jesús Moratalla-López; José Francisco Palacios-Abella; Isabel López-Heras; Carlos Rochera; Antonio Picazo; Antonio Camacho; Andreu Rico (Ecotoxicology, 2026)
Mediterranean wetlands are exposed to multiple environmental stressors, including chemical pollution from agricultural practices. Difenoconazole, an azole fungicide used in rice fields to control rice blast, may reach concentrations in Mediterranean wetlands that exceed toxicity thresholds for aquatic organisms. However, its long-term effects on freshwater communities are still poorly understood. This study evaluated the impact of difenoconazole on zooplankton and macroinvertebrate communities using outdoor freshwater mesocosms that simulated Mediterranean wetland conditions over 90 days. Two ecological conditions were tested: vegetated mesocosms containing Myriophyllum spicatum and non-vegetated mesocosms. Four exposure concentrations were applied twice, with a 14-day interval: control (0 µg/L), low (2 µg/L), medium (20 µg/L), and high (200 µg/L). Difenoconazole caused significant effects on zooplankton and macroinvertebrate communities at concentrations above 20 µg/L. Cladocerans and copepods were particularly sensitive, with some population reductions observed even at 2 µg/L. Among macroinvertebrates, the snail family Planorbidae showed declines at concentrations above 2 µg/L, while the freshwater shrimp Dugastella valentina was affected at concentrations exceeding 20 µg/L. The presence of macrophytes slightly mitigated pesticide effects by enhancing their dissipation from the water column. Indirect effects were also detected, including increased chlorophyll-a concentrations at the highest concentration, suggesting reduced zooplankton grazing pressure. Overall, the results indicate that the chronic threshold value for difenoconazole derived from species sensitivity distributions obtained from the literature is generally protective under semi-field conditions. However, peak exposures in rice fields and drainage ditches may significantly reduce the abundance of some invertebrate taxa under Mediterranean conditions.